The Assessment of Effect of Fish Myofibrillar Protein-Nanofibrillated Cellulose Edible Film Incorporated with Oregano Essential Oil Nanoliposomes on Microbial Quality of Rainbow Trout Fillet during Cold Storage - Mohsen Kazemi; Bahare Shabanpour; Parastoo Pourashouri (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2018)
In this study, bionanocomposite films enriched with Oregano essential oil (OEO) and OEO nanoliposomes (2% v/v) as a preservative agent on the rainbow trout fillets were used. Trout fillets were separated into four groups: unwrapped trout fillet (control), wrapped with nanocomposite based fish myofibrillar protein (FMP)-nanofibrillated cellulose (NFC) and wrapped with nanocomposites incorporated with 2% (v/v) OEO and OEO nanoliposomes. Trout fillets were analyzed for microbiological (total viable count, psychrotrophic count, Pseudomonas spp. counts and Enterobacteriaceae counts), sensory and color characteristics. The results of microbiological analysis showed that the highest rate of growth was observed respectively in trout fillets stored in air (control), wrapped with FMP-NFC nanocomposite and the lowest counts were in wrapped samples with nanocomposite enriched with OEO and OEO nanoliposomes (P<0.05). In this regard, the films enriched with OEO and OEO nanoliposomes increased the microbial shelf life for 4 days (up to 12). The wrapped sample by film enriched with OEO nanoliposomes, especially in the early to middle (day 10) storage time, for microbiological characteristics were better than the film contain OEO. Compared to control samples, fillet samples wrapped with activated films showed less change in sensory and color (L*, a *andb*) characteristics during storage (P<0.05).